Pembuatan Komposit Serat Batang Pisang Kepok Bermatriks Polyester Dengan Metode Vacuum Bagging - Hutagaol, Martiandes; Fatra, Warman; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Various types of bananas with good quality thrive in various regions in Riau. Banana fiber has good potential to be developed as an engineering material by engineering composite materials. The making of composites using kepok banana stem fiber was carried out using the vacuum bagging method. The fiber was heated with temperature variations of 70 ° C, 80 ° C and 90 ° C and time of 2, 3 and 4 hours, then the fiber was extracted with a length of 30 cm. The composite fiber arrangement is continuous. To determine the experimental design and variables that have a significant effect on tensile strength, flexural strength and impact resistance, the statistical method Response Surface Methodology (RSM) is used. The results showed that the increased tensile strength was significantly influenced by the volume fraction of banana fiber, temperature and heating time of the fiber. The highest tensile strength value of 89.855 MPa and the highest flexural strength value of 327.76 MPa were obtained at a volume fraction of 38% banana fiber, heating temperature 70 ° C and heating time of 4 hours. The highest impact resistance value of 2.56 J was obtained at a volume fraction of 28% banana fiber, heating temperature of 70 ° C and heating time of 2 hours.Keywords: Banana Fiber, NaOH, Response Surface Methodology, Vacuum Bagging.